2017
DOI: 10.1155/2017/1050749
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Weight Management Practices among Adults in the United Arab Emirates

Abstract: With a rise in global incidence of overweight and obesity, the number of patients seeking weight management (WM) advice is likely to increase. Our aim was to explore the prevalence of WM practices and investigate association of WM goals with sociodemographic variables and practices among United Arab Emirates (UAE) adults. An exploratory, cross-sectional research was conducted on 1275 adult males and females, residing in UAE. A structured questionnaire was administered. WM goals to lose/maintain/gain weight wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This study showed that 50 per cent of the participants were able to meet the recommended weight reduction target, with the majority seen in the participants less than 40 years, and this was corroborated by the report by Atlee et al, in 2017. 41 There was a female preponderance observed among those who were able to achieve target weight reduction similar to a study by Andreyeva et al, 42 with most weight reduction in unmarried participants which was contradictory to an exploratory study with a cross-sectional study design, in which more married participants reduced in weight. 41 Those participants who had greater than or equal secondary school education in this study reached the target for weight reduction.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…This study showed that 50 per cent of the participants were able to meet the recommended weight reduction target, with the majority seen in the participants less than 40 years, and this was corroborated by the report by Atlee et al, in 2017. 41 There was a female preponderance observed among those who were able to achieve target weight reduction similar to a study by Andreyeva et al, 42 with most weight reduction in unmarried participants which was contradictory to an exploratory study with a cross-sectional study design, in which more married participants reduced in weight. 41 Those participants who had greater than or equal secondary school education in this study reached the target for weight reduction.…”
Section: Discussionmentioning
confidence: 69%
“…41 There was a female preponderance observed among those who were able to achieve target weight reduction similar to a study by Andreyeva et al, 42 with most weight reduction in unmarried participants which was contradictory to an exploratory study with a cross-sectional study design, in which more married participants reduced in weight. 41 Those participants who had greater than or equal secondary school education in this study reached the target for weight reduction. This observation was not supported by the report by Barbering et al, in 2018, in which it was found that education was not related to trying to reduce weight.…”
Section: Discussionmentioning
confidence: 69%
“…Inclusion criteria: Apparently healthy adolescent's students aged (11)(12)(13)(14)(15)(16)(17)(18)(19) years, attending governmental preparatory and secondary schools. Exclusion criteria: private or international preparatory and secondary schools.…”
Section: Methodsmentioning
confidence: 99%
“…11 The popularity of unhealthy weight loss practice is problematic because they are not often effective, and may cause adverse effect on health and not recommended by health professionals. 12 The aims of the study are to assess weight loss practice either (healthy or unhealthy) among adolescents, to determine association between some personal factors and weight loss practice and to know sources of their information.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid potential confounders, such as the avoidance of nuts for caloric control or health issues, we included several exclusion criteria including the presence of any disease, food allergy, or intolerance; the consumption of a special diet; or dietary restrictions, such as a vegetarian diet. In this pilot study, we recruited only male consumers due to the higher prevalence of strategies to lose weight for women compared to men [15,16]. Dieting, calorie counting, and avoiding fatty foods are among the various body-weight control behaviors observed in women [16][17][18].…”
Section: Recruitment and Enrollmentmentioning
confidence: 99%